Prevalence of Gestational Diabetes Mellitus in Obstetric patients using Macrosomia and Increased Amniotic Fluid on Ultrasound, as Diagnostic Markers - Nazia Hakeem, Yasmin Akhtar, Khush Bakht, Sanobar Ashfaq, Uzma Ahmed, Sanjay Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the prevalence of gestational diabetes in obstetric patients with the help of ultrasonography and diagnostic biomarkers such as increased amniotic fluid and macrosomia. Methods: In 110 women who failed the glucose tolerance test, longitudinal ultrasound measurements of foetal growth were taken during the first, second and third trimesters with the informed consent of every pregnant women. 524 ultrasound examinations were performed in total, and uncomplicated pregnancies were included as controls for the comparison of our results. Head circumference (HC), abdominal circumference (AC), femur length (FL), and head circumference to abdominal circumference ratio (HC/AC) was evaluated at 17th and 37th weeks of gestation while amniotic fluid was measured and recorded at 13th, 27th and 37th weeks of gestation respectively. Results: The mean HbA1c (%) of the pregnant women in 1st semester recorded was 5.2±0.27SD which increased to 5.31 ±0.24SD in 2nd trimester and later changed to 5.54±0.17SD in 3rd semester. The measured amniotic fluid in ultrasound was 23.23cm ±3.18 SD at 13th weeks of gestation, 15.97cm±2.62SD at 27th weeks and 11.95cm±1.99SD at 37th week. The mean abdominal circumference at 37th week was 347.01mm ±7.28SD, mean head circumference was 1477.50mm±2.88SD, AC/HC ratio at 37th week estimated 0.89 ±0.08SD and femur length was 73.44mm ±2.28SD respectively. Conclusion: The finding suggests that increased amniotic fluid and macrosomia are important biomarkers of gestational diabetes and can be assessed through ultrasonography.